Structural balancing : - Wright, Kyle C. (McGraw-Hill, 2011)
Suitable for clinical courses in massage therapy, physical therapy, and chiropractic programs, this guide advances the reader's clinical knowledge and skills of trigger point therapy techniques, postural and body structural conditions that cause chronic pain and discomfort, and specific therapies and exercises for resolving those conditions